Pengembangan dan Implementasi Smart Campus Berbasis Smart Card Di Institut Agama Islam Negeri Bone - Intan Sari Areni; Elyas Palantei; Ansar Suyuti; Merna Baharuddin; Faisal Arya Samman; Dewiani -; Wardi -; Adnan -; Andi Ejah Umraeni (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2019)
The purpose of this service is to develop and implement Smart Card-based Smart Campus at the State Islamic Institute (IAIN) Bone. This application platform was developed using the standard Indonesian Smart Card Consortium (KSCI) with a smart card and reader chipset from PT Xirka Silicon Technology and PT. INTI. This application serves to receive, process, and visually display data sent by a card reader. Processing this data is very necessary so that the data collected can be used to facilitate the campus in recording student data electronically and use it for various campus interests. In addition, this application allows access to interoperability with applications on other campuses, for example with fellow KSCI member campuses or other campuses in this case the IAIN Bone campus. When this smart card system is running and stable, the system can be developed to enter various other applications such as ticketing, loyalty cards in various communities, and close loop payments. The implementation of community service was divided into 2 stages, namely the socialization stage about smart campus, especially smart cards and the Smart Card-based Smart Card application training phase on the IAIN Bone campus. The implementation of this activity received a positive response from the campus and has implemented two smart card systems in the campus of IAIN Bone.